Aggregated crime survey for England and Wales, 1982-2017, with access to justice focus - Impara, E. (UK Data Service, 2020)
his aggregated and appended subset of the Crime Survey for England and Wales (CSEW) was compiled as part of the ESRC project Victims' Access to Justice through English Criminal Courts, 1675 to the present. The project addresses a pressing need within the current criminal justice system: to find means of securing broader public access to justice defined as the right and ability of a person to seek formal acknowledgement and redress of wrongs committed against them within a given legal system. This special dataset gathers variables from the CSEW about the Criminal Justice System (CJS), socio-demographic information and some victimisation details, extends and aggregates them. The study was also influenced by the work of Farrall et al. (2013), held under SN 7875 - Long-Term Trajectories of Crime in the United Kingdom, 1982-2013. Further information can be found in the documentation.